Food aid supply and distribution in insecure regions: world food programme operation analysis in Ethiopia - Leiras, Adriana; Gonçalves, Paulo; Chawaguta, Bervery; Junior, Irineu De Brito [UNESP]; Yoshizaki, Hugo Tsugunobu Yoshida (FapUNIFESP (SciELO), 2021)
Paper aims: This paper analyzes the food aid supply and distribution for famine relief by the World Food Programme (WFP) in Ethiopia. Food insecurity has increasingly affected people around the world. Furthermore, the characteristics of the provision of humanitarian aid in insecure regions pose several additional challenges over traditional distribution planning (e.g., corruption, losses in last-mile distribution, security escorts). Originality: Most previous studies addressing famine relief are qualitative, with only a handful including mathematical modeling as this work. Furthermore, we validate our mathematical model with data from a real problem setting. Research method: We propose a stochastic transshipment network flow model to ensure the efficient allocation of limited resources. Main findings: The results show high potential for cost savings and offer managerial insights to humanitarian logisticians on the food aid supply and distribution. Our findings indicate that policies in humanitarian logistics should focus on: (a) relaxing legislation for customs clearance of humanitarian supplies; (b) strengthening local market to increase local procurement; (c) implementing tools to enhance security; and (d) monitoring distribution to mitigate the impact of corruption. Implications for theory and practice: The results suggest that optimizing food aid distribution in Ethiopia can save millions of people vulnerable to malnutrition.
Keywords: Humanitarian logistics. Food aid supply. Food aid distribution. Stochastic optimization. Famine relief